1996
DOI: 10.1172/jci118891
|View full text |Cite
|
Sign up to set email alerts
|

Identification of targets of leptin action in rat hypothalamus.

Abstract: The hypothesis that leptin (OB protein) acts in the hypothalamus to reduce food intake and body weight is based primarily on evidence from leptin-deficient, ob/ob mice. To investigate whether leptin exerts similar effects in normal animals, we administered leptin intracerebroventricularly (icv) to Long-Evans rats. Leptin administration (3.5 g icv) at the onset of nocturnal feeding reduced food intake by 50% at 1 h and by 42% at 4 h, as compared with vehicletreated controls (both P Ͻ 0.05). To investigate the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
830
5
25

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,396 publications
(903 citation statements)
references
References 34 publications
(30 reference statements)
43
830
5
25
Order By: Relevance
“…In the present study, we found that leptin directly increased the mRNA levels of both CRF and Ucn2/3 in hypothalamic N39 cells, indicating that leptin acts directly on CRF and Ucn2/3 neurons via the Ob-Rb in the hypothalamus. Both in vivo and in vitro studies have shown that leptin increases expression of CRF in the hypothalamus [12,28,43,54]. In fact, simultaneous injection of leptin and a non-specific CRF receptor antagonist confirmed that a ligand for CRF receptor contributes to leptin's anorectic effect [21,59].…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we found that leptin directly increased the mRNA levels of both CRF and Ucn2/3 in hypothalamic N39 cells, indicating that leptin acts directly on CRF and Ucn2/3 neurons via the Ob-Rb in the hypothalamus. Both in vivo and in vitro studies have shown that leptin increases expression of CRF in the hypothalamus [12,28,43,54]. In fact, simultaneous injection of leptin and a non-specific CRF receptor antagonist confirmed that a ligand for CRF receptor contributes to leptin's anorectic effect [21,59].…”
Section: Discussionmentioning
confidence: 95%
“…It had been shown that direct delivery of leptin to the lateral or third ventricle suppresses food intake up to 24 h after treatment (156,192). The finding was consistent with the hypothalamic model, but did not rule out the possibility of extrahypothalamic contribution.…”
Section: Interoceptorsmentioning
confidence: 87%
“…Interestingly, leptin appears to be both upstream and downstream of hypothalamic CRF 2 action, perhaps providing a physiological context for the current findings. Leptin has receptors on CRFergic hypothalamic neurons (Hakansson et al, 1998), provokes secretion of CRF receptor agonists from hypothalamic explants (Costa et al, 1997;Raber et al, 1997), and stimulates PVN CRF (Schwartz et al, 1996) and VMH CRF 2 mRNA synthesis (Hashimoto et al, 2004). Conversely, Zucker obese (fa/fa) rats, which lack a fully functional leptin receptor, have reduced VMH CRF 2 mRNA expression (Richard et al, 1996).…”
Section: Discussionmentioning
confidence: 99%